2015
DOI: 10.1186/s12889-015-1390-5
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and attitude of key community members towards tuberculosis: mixed method study from BRAC TB control areas in Bangladesh

Abstract: BackgroundBangladesh National Tuberculosis (TB) Control Programme adopted a number of strategies to facilitate TB diagnosis and treatment. ‘Advocacy, Communication and Social Mobilization’ (ACSM) was one of the key strategies implemented by BRAC (Bangladesh Rural Advancement Committee, a non-governmental development organization) TB control program. The purpose of this study is to assess the knowledge and attitudes of the key community members (KCMs) participated in ACSM in BRAC TB control areas.MethodsThis st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
2
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 14 publications
2
18
2
3
Order By: Relevance
“…Desse modo, tal fato corrobora os resultados obtidos em estudos nacionais e internacionais realizados com trabalhadores de sistemas carcerários e de saúde, indivíduos privados de liberdade (6) , familiares de pessoas em tratamento da TB (8) e com a comunidade em geral (9,11) , os quais reforçam a necessidade da educação em saúde. Isso indica a necessidade de intervenção capaz de mudar o perfil epidemiológico de doenças, especialmente as transmissíveis.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Desse modo, tal fato corrobora os resultados obtidos em estudos nacionais e internacionais realizados com trabalhadores de sistemas carcerários e de saúde, indivíduos privados de liberdade (6) , familiares de pessoas em tratamento da TB (8) e com a comunidade em geral (9,11) , os quais reforçam a necessidade da educação em saúde. Isso indica a necessidade de intervenção capaz de mudar o perfil epidemiológico de doenças, especialmente as transmissíveis.…”
Section: Discussionunclassified
“…Mesmo que o ambiente prisional contribua para o maior risco de contágio, há também a oportunidade de diagnóstico e tratamento, o que trará benefícios à saúde não só do detento, mas também dos profissionais do sistema prisional, dos familiares e da comunidade em que o detento voltará a ter convívio (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). Porém, para que as ações em saúde sejam bem sucedidas, as condições de vida, as limitações estruturais dos presídios e as fragilidades dos serviços de saúde necessitam serem revistas e melhoradas (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) . Entretanto, outro estudo (2) , realizado em cinco prisões do Sistema Penitenciário de dois municípios do Pará, enfatizou que a pessoa privada de liberdade é capaz de entender a sua condição e ultrapassar as dificuldades para o alcance da cura da doença.…”
Section: Discussionunclassified
“…1,2 It is reported that, globally, about 9 million people developed tuberculosis and about 1.5 million people died due to tuberculosis across the globe in 2013. The estimate number of incident TB cases in India are 2.6 million during the same period.…”
Section: Introductionmentioning
confidence: 99%
“…5 Various kinds of the stigma associated with tuberculosis and poor knowledge in the community on various important aspects of the disease are responsible for this. 2,6 Many previous studies conducted in the past have documented very poor public awareness regarding tuberculosis. [7][8][9][10][11][12][13][14] Low awareness levels were documented for various important aspects of the disease including mode of transmission, prevention methods, treatment services etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation